Endoscopic Management of a Proximally Migrated Fully Covered SEMS Using the Stent-in-Stent Technique - Arunchai Chang; Varayu Prachayakul (Case Reports in Medicine)
Endoscopic biliary decompression via stent placement is an important approach for the palliative management of distal malignant biliary obstruction. However, migration of the inserted stent can occur, either distally or proximally; proximal migration is less common, but it also presents a greater challenge for endoscopic resolution. We present a case of a 67-year-old woman who had locally advanced pancreatic cancer and developed a common bile duct obstruction. Upon clinical presentation of chronic, painless, progressive jaundice, the obstruction was managed by placing of a 10 mm × 60 mm covered self-expandable metal stent (CSEMS), which successfully facilitated palliative biliary drainage. Six months later, however, the patient developed recurrent jaundice, which was determined to be due to proximal migration of the CSEMS. Repeat endoscopic retrograde cholangiography was performed, and initial attempts to retrieve the migrated stent failed. Finally, another 10 mm × 60 mm CSEMS was placed across the stricture site, inside the previous stent, which remained in place. The treatment resolved the obstruction and jaundice, and the patient experienced no adverse events.